Genomic insights into a population of introduced European rabbits Oryctolagus cuniculus in Australia and the development of genetic resistance to rabbit hemorrhagic disease virus. Issue 2 (16th March 2021) - Elfekih, Samia; Metcalfe, Suzanne; Walsh, Tom K.; Cox, Tarnya E.; Strive, Tanja
Abstract: The European rabbit ( Oryctolagus cuniculus ) is one of the most devastating invasive species in Australia. Since the 1950s, myxoma virus (MYXV) and rabbit haemorrhagic disease virus (RHDV) have been used to manage overabundant rabbit populations. Resistance to MYXV was observed within a few years of the release. More recently, resistance to lethal RHDV infection has also been reported, undermining the efficiency of landscape‐scale rabbit control. Previous studies suggest that genetic resistance to lethal RHDV infection may differ locally between populations, yet the mechanisms of genetic resistance remain poorly understood. Here, we used genotyping by sequencing (GBS) data representing a reduced representation of the genome, to investigate Australian rabbit populations. Our aims were to understand the relationship between populations and identify possible genomic signatures of selection for RHDV resistance. One population we investigated had previously been reported to show levels of resistance to lethal RHDV infection. This population was compared to three other populations with lower or no previously reported RHDV resistance. We identified a set of novel candidate genes that could be involved in host–pathogen interactions such as virus binding and infection processes. These genes did not overlap with previous studies on RHDV resistance carried out in different rabbit populations, suggesting that multiple mechanisms are feasible. These findings provide useful insights into the different potential mechanisms of genetic resistance to RHDV virus which will inform future functional studies in this area.